Low-cost high-throughput targeted sequencing for the accurate detection of respiratory tract pathogens - Changyan Ju; Chengbosen Zhou; Zhezhi Deng; Jingwei Gao; Weizhao Jiang; Hanbing Zeng; Haiwei Huang; Yongxiang Duan; David X Deng (Journal of Infection in Developing Countries)
Introduction: The current gold standard for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnosis by real-time reverse transcriptase polymerase chain reaction (RT-PCR) is limited by the number of genes that can be detected. In this study, we developed a low-cost and high-throughput next-generation sequencing technology that can overcome the limitations of real time RT-PCR.